Pemanfaatan Pupuk Ferti One Plus Untuk Pertumbuhan Tanaman Rotala Rotundifolia (Buch-ham.Ex roxb.) - Ezward, Chairil; Dinova, Alfito; Wahyudi, Wahyudi (Jurusan Budidaya Pertanian Fakultas Pertanian Universitas Andalas, 2024)
Aquascape is an artistic activity in arranging and planting water plants, rocks and wood aesthetically in an aquarium so as to provide an underwater gardening effect. Rotala rotundifolia (Buch.-Ham. ex Roxb.) Koehne is one of the Lythraceae family and is an aquatic plant. Ferti One plus fertilizer is a concentrated liquid fertilizer with a formula containing all the essential micro nutrient elements Boron (Bo), Chlorine (Cl), Copper (Cu), Iron (Fe), Manganese (Mn), Molybdenum (Mo), Nickel (Ni). ), Zinc (Zn), Aluminum (Al), Cobalt, Selenium, Silicon (Si), Sodium and enriched with stabilized iron complex. This research aims to determine the appropriate concentration of Ferti One Plus fertilizer on the growth of Rotala Rotundifolia (Buch.-ham. Ex roxb.) plants. The design used in this research was a non-factorial Completely Randomized Design (CRD) consisting of 4 treatments, the study consisted of P0 (No Ferti One Plus Fertilizer), P1 (Ferti One Plus Fertilizer 2.5 ml/liter), P2 (Fertilizer ferti one plus 5 ml/liter) and P3 (Ferti one plus fertilizer 7.5 ml/liter). Based on the results of research on giving concentration of Ferti One Plus fertilizer, it can be concluded that giving P3 (Ferti One Plus Fertilizer 7.5 ml/liter) is the best for plant height and root length, namely height 25.18 cm and root length 4 cm. However, it had no real effect on plant fresh weight and stem diameter in rotala rotundifolia plants.